Rational design of tetrahydrogeraniol-based hydrophobically modified poly(acrylic acid) as emulsifier of terpene-in-water transparent nanoemulsions. (September 2017) - Atanase, Leonard-Ionut; Larraya, Carlos; Tranchant, Jean-François; Save, Maud
Graphical abstract: Highlights: Reversible Addition Frangmentation Poylmerization (RAFT) of acrylic acid. Renewable resources. Tetrahydrogeraniol hydrophobically modified poly(acrylic acid) emulsifier. Amphiphilic copolymer self-assembly in water. Terpene-in-water transparent nanoemulsion. Abstract: Amphiphilic copolymers based on renewable resources were involved as emulsifiers to prepare transparent terpene-in-water nanoemulsions. The amphiphilic copolymers are composed of hydrophobically modified poly(acrylic acid) (HMPAA) grafted with different fractions of hydrophobic bio-based tetrahydrogeraniol (THG) side chains. The well-defined PAA were synthesized by reversible addition fragmentation transfer (RAFT) polymerization in order to tune the number-average molar mass of the initial PAA. The self-assembly in aqueous solution of the HMPAA copolymers was investigated through the measurement of their critical aggregation concentration by viscometry, tensiometry, dynamic light scattering and the determination of their aggregation number by static light scattering. Series of oil-in-water nanoemulsions using dihydromyrcenol (DHM) terpene as dispersed phase and PAA-THG as emulsifier were prepared with different PAA-THG/DHM weight ratios and DHM/water weight ratios. The level of transparency of the emulsions was monitored though the transmittance value measured at 600 nm and the measurements of the hydrodynamic diameter of droplets by dynamic light scattering. This study highlights that the structure of the PAA x -THG y is a key parameter to prepare terpene-in-water nanoemulsions with the required high level of transparency. The optimised structure of the emulsifier consists in a moderate degree of polymerization of PAA backbone ( DP ‾ n, PAA ≤ 180 ) along with an intermediate average degree of substitution in hydrophobic THG side chains (13 ≤ DS ‾ ≤ 32).